Pengaruh Modular Object-Oriented Dynamic Learning Environment (Moodle) Terhadap Hasil Belajar Siswa Pada Materi Sistem Pencernaan Manusia di Kelas VII MTsN Cikatomas: Pengaruh Modular Object-Oriented Dynamic Learning Environment (Moodle) Terhadap Hasil Belajar Siswa Pada Materi Sistem Pencernaan Manusia di Kelas VII MTsN Cikatomas - Dani Ramdani (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2016)
The purpose of this research was to determine the influence of Modular Object-Oriented Dynamic Learning Environment (MOODLE) to student result learning outcomes in the human digestive system in 7th grade MTs N Cikatomas. This research was conducted in September to November 2014 in MTs N Cikatomas Tasikmalaya. Research method used the true experimental with the population was from all classes on 7th grade as many as 5 classes with the number of students as many as 186 students. The sample was used are 2 classes that selected by the cluster random sampling technique. To measure learning outcomes used 40 questions learning outcomes instrument. Technique of analyzing the data in this research using t-test with significant level Î± = 0,05. Based on data analysis and hypothesis testing be concluded that there is influence of Modular Object-Oriented Dynamic Learning Environment (MOODLE) to student result learning outcomes in the human digestive system in 7th grade MTs N Cikatomas.